REKULTURASI PENEGAK HUKUM DALAM PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA TRAFFICKING - Carolina Carolina (Masalah-Masalah Hukum, 2013)
Trafficking crime is extraordinary crime (extra-ordinary crime) derived from a compilation of socio-economic problems that developed in the community. Trafficking in law enforcement approach should be re improvement of the legal culture law enforcement officers of character positivism towards developing a mindset renewal based on the desire to find justice substantive crime prevention and enforcement trafficking. This study aimed to the general objective of this research is to find and evaluate the problems of law enforcement in dealing with human trafficking crime that has been done so far tend not optimal to find the factors that inhibit the ideal pattern of development and seek legal culture of law enforcement officers. The results of this study indicate that the handling offense by law enforcement officers is not optimal and need renewal paradigm of law enforcement officers when dealing with trafficking cases.